Paessler Router Traffic Grapher (PRTG) Network Monitoring: An Implementation Process in Vitrox (Journal of Digital System Development, 2024)
Network monitoring is crucial for providing network administrators with the information to ensure optimal real-time performance. The expansion of ViTrox from Campus 2.0 to Campus 3.0 requires a network monitoring system for better management and analysis of its infrastructure. Paessler Router Traffic Grapher (PRTG) Network Monitor has been selected to oversee ViTrox's network traffic using SNMP to address this need and ensure comprehensive network oversight. ViTrox can effectively manage and analyze its network traffic, ensuring optimal performance and reliability as it transitions to the new campus setup. The SNMP manager initiates communication using this communication protocol, and the agent responds. PRTG employs a sensor-based approach, defining a single metric on a device based on the required data volume, which allows for real-time monitoring and analysis. To implement PRTG, the waterfall model methodology is employed to ensure the project's step-by-step completion. Critical devices are selected for monitoring, and alarm notifications are configured to alert administrators when a sensor falls below the threshold. Utilizing this network monitoring tool allows for prompt tracking of any network downtime, providing details such as time, location, and duration. Performance metrics analysis is used as the project evaluation method to measure the key performance indicators (KPIs) such as system uptime and the accuracy of alerts. The project's significance is in providing real-time visibility, enabling proactive issue detection, and optimizing resource management. The future direction of implementing PRTG Network Monitor involves expanding its capabilities to adapt to evolving network needs and technological advancements.